ERS-USM TO PROVIDE SUPPORT FOR DISASTERAFFECTED TELECOMMUNICATION SYSTEMS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, KELANTAN, 23 September 2016 – The Emergency Radio System Universiti Sains Malaysia (USM) ERSUSM has been successfully developed by a lecturer from the Department of Emergency Medicine, School of Medical Sciences, Dr. Mohd Shaharudin Shah Che Hamzah.